Design of Ultra-Wideband Antenna With Bandpass Filtering Capability - Qasem Ahmed, Sharif Ahmed (2020)
Nowadays, a demand for wireless communication systems with ultra-high data rates and multimedia with higher bandwidth, is increased. This demand takes the researchers attention to focus on antennas with wide bandwidth and high data rates. This work presents an integration of ultrawideband (UWB) antenna and microwave bandpass filter for wireless applications. The traditional configuration of the antennas and filters are designed separately and connected by coaxial cable which increases the size, and manufacturing cost. Furthermore, the cable connected between the antenna and filter introduces losses that degrades the overall wireless system performance. Thus, an integration of the antenna and filter would bring many benefits such as reduction in the cost and physical size, and improvement in wireless system performance. Recently, some research works on the integration of filter and antenna have been carried out. The integration of the antenna and filter into a single unit has reduced the size and the cost in comparison to the traditional filter and antenna designs. However, these filtering antenna designs suffer from narrow impedance bandwidth. Moreover, some filtering antenna designs suffer from low realised gain. Based on the limitations of past research studies on filtering antenna, this work proposes a new design of integrated UWB filtering antenna. The proposed design consists of modified UWB antenna and UWB bandpass filter designed based on multi-mode resonator technique. First, UWB antenna and bandpass filter are designed separately, in CST software, to ensure their performance. Secondly, these two designs are integrated into a single unit on the same substrate of Roger RO4003C with loss tangent of 0.0027, permittivity of 3.38 and thickness of 1.524 mm. Then, integration of single modified UWB antenna and multimode resonator filter is carried out. Furthermore, UWB antenna array is integrated with multi-mode resonator bandpass filter to further enhance filtering antenna realised gain. The designs are fabricated in the laboratory, and the simulated and measured results are analysed.